2009
DOI: 10.1073/pnas.0906463106
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of ubiquitin conjugates in a polyglutamine disease model occurs without global ubiquitin/proteasome system impairment

Abstract: Aggregation-prone proteins have been suggested to overwhelm and impair the ubiquitin/proteasome system (UPS) in polyglutamine (polyQ) disorders, such as Huntington's disease (HD). Overexpression of an N-terminal fragment of mutant huntingtin (NmutHtt), an aggregation-prone polyQ protein responsible for HD, obstructs the UPS in cellular models. Furthermore, based on the accumulation of polyubiquitin conjugates in brains of R6/2 mice, which express human N-mutHtt and are one of the most severe polyQ disorder mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 48 publications
7
63
0
1
Order By: Relevance
“…However, N-mutHttinduced UPS impairment in vivo is transient and, in good agreement with previous reports combining PolyQ mouse models with the same (Bowman et al, 2005;Maynard et al, 2009) or similar (Bett et al, 2009) reporter mice, it is not detected with constitutive N-mutHtt expression in adult mice. Finally, that aggregate formation correlates with UPS recovery had also been recently reported in a cell model (Mitra et al, 2009), and here we were able to demonstrate causality with the use of antiaggregation compounds in a cell model and also in vivo in mouse models.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, N-mutHttinduced UPS impairment in vivo is transient and, in good agreement with previous reports combining PolyQ mouse models with the same (Bowman et al, 2005;Maynard et al, 2009) or similar (Bett et al, 2009) reporter mice, it is not detected with constitutive N-mutHtt expression in adult mice. Finally, that aggregate formation correlates with UPS recovery had also been recently reported in a cell model (Mitra et al, 2009), and here we were able to demonstrate causality with the use of antiaggregation compounds in a cell model and also in vivo in mouse models.…”
Section: Discussionsupporting
confidence: 77%
“…However, similar studies on mouse models failed to detect UPS impairment either by measuring proteasome activity in brain extracts (Diaz-Hernandez et al, 2003;Bett et al, 2006) or by using UPS reporter mice that express specifically designed proteasome substrates (Bett et al, 2009;Maynard et al, 2009). Moreover, we have recently shown that the increase in polyubiquitin conjugates in the brain of R6/2 mice (Bennett et al, 2007) occurs in the absence of a general UPS impairment .…”
Section: Introductionmentioning
confidence: 99%
“…Although this model is consistent with data showing a strong correlation between mutant htt aggregation and accumulation of synthetic short-lived substrates of the UPS in cell culture (Bence et al, 2001;Bennett et al, 2005), these UPS substrate reporters do not accumulate (Bett et al, 2009;Maynard et al, 2009) or only accumulate transiently (Ortega et al, 2010) in mouse models of HD. In cell culture, mutant htt aggregation and recruitment of Ub conjugates to nascent IBs is not temporally correlated with accumulation of UPS reporters (Hipp et al, 2012).…”
Section: Introductionsupporting
confidence: 77%
“…A recent study also suggested that toxic htt forms do not impair the proteasome and that, instead, the impairment of the UPS arises from the accumulation of N-terminal fragments [200]. Supporting this model, an HD mouse study showed no global impairment of UPS activities, and the forms of polyubiquitylated proteins accumulated in this model were of a different nature than those found upon proteasome inhibition [201]. In contrast, impairment of the UPS was demonstrated in transfected HEK293 cells upon polyQ aggregation, even before inclusion of body formation [183].…”
Section: The Ups In Neurodegenerative Disordersmentioning
confidence: 72%